Discussing sudden unexpected death in epilepsy with children and young people with epilepsy and their parents/carers: A mixed methods systematic review. (May 2020) - Cooper, Kay; Kirkpatrick, Pamela; Brand, Celia; Rolfe, Alix; Florida-James, Sarah
Highlights: SUDEP information should be provided at or close to the time of epilepsy diagnosis. SUDEP information should be provided face-to-face in the clinic or home setting. A specialist known to the child/young person should provide SUDEP information. Patients want information on prevalence, risk factors and risk reduction measures. Abstract: Purpose: To synthesise the quantitative and qualitative evidence on the views and experiences of children and young people with epilepsy (CYPwE), their family members/caregivers and healthcare professionals on conversations between healthcare professionals and CYPwE/caregivers about the possibility of sudden unexplained death in epilepsy (SUDEP). Methods: Mixed methods systematic review in accordance with Joanna Briggs Institute methodology, PRISMA guidelines and guided by an a-priori protocol. Results: 656 potentially relevant studies were identified, 11 of which fulfilled the inclusion criteria for the review: 6 quantitative studies, 4 qualitative studies and 1 opinion/text article. Data synthesis resulted in the following 2 integrated findings: (i) Caregivers, and where appropriate CYPwE, should be provided with information on SUDEP and how it relates to them; (ii) Information on SUDEP should be delivered face-to-face, with supporting written information, by a suitably knowledgeable healthcare professional whom the caregiver/CYPwE feels comfortable with, at an appropriate time at or close to diagnosis. Conclusion: This review confirms that healthcare professionals should discus SUDEP with CYPwE and/or their caregivers at or around the time of diagnosis and that the discussion should include prevalence of SUDEP, risk factors and risk reduction methods relative to the individual concerned. Apart from delivering SUDEP information face-to-face, with written or online information provided to reinforce messages, there is a lack of evidence on "how" to impart this sensitive information. Further research exploring the most acceptable and effective methods of discussing SUDEP with CYPwE and their caregivers is therefore indicated.